Effects of a Text-Writing Fluency Intervention for Postsecondary Students with Intellectual and Developmental Disabilities. Issue 4 (8th August 2021) - Rodgers, Derek B.; Datchuk, S. M.; Rila, A. L.
ABSTRACT: Writing has implications for the academic, vocational, and social pursuits of students. Unfortunately, many students with disabilities – including those with intellectual and developmental disabilities – struggle with a foundational aspect of written expression: text writing within sentences and paragraphs. This study used a multiple-baseline across students' design to investigate the effects of a multicomponent intervention, explicit instruction with timed practice, on the fluent sentence text writing or sentence construction of four postsecondary students with intellectual and developmental disabilities. We tested effects on sentence text writing measures and application to paragraph text writing. Data were analyzed through visual analysis and Tau-U effect sizes. The results of the intervention suggest that the multicomponent intervention had mixed effects on the sentence text and paragraph text writing of students. How the study contributes to the broader writing literature is discussed and limitations are presented.